Avaliação do processo de vulcanização inversa visando a aplicação na produção de fertilizantes - Valle, Stella Fortuna do (2018)
Sulfur (S) is an essential macronutrient for crop development, nevertheless, its deficiency in agricultural soils has become increasingly alarming in the last decades. Despite elemental sulfur (S8) being a widely utilized commercial alternative, plant uptake is only possible after its biological oxidation to sulfate (SO42-), a slow process that considerably reduces the compounds efficiency. The present research proposed the synthesis of a new sulfur fertilizer based on the chemical modification of S8 rings into a linear structure, more available to the oxidizing microorganisms. In order to do that, the copolymerization technique entitled inverse vulcanization was conducted, which resolves S8 processing issues while also applying environmentally sustainable principles. Chemically stable and functional polymeric-sulfur products were obtained via copolymerization between S8 and soybean oil, and copolymers with porous structure were also prepared using NaCl as porogen agent. Physical-chemical characterizations exhibited the structural and morphological changes. FTIR showed the absence of bands related to C=C bonds in the products spectra and the appearance of S-S stretching band, while XRD exhibited the materials amorphous character. DSC revealed that part of the sulfur was not converted into the polymer, remaining dispersed in the matrix as S8. Oxidation experiments in submerged cultivation with A. niger proved the polymeric-sulfur materials are capable of significantly improving the oxidation process, with percentages more than 50% superior than the ones reached by S8. The oxidation test in soil revealed that the porous structure greatly enhanced the polymer efficiency, producing 1818% more sulfate than S8 in 58 days of incubation. The hydrocarbon content in the materials also contributed for the better performance as a source of carbon and energy for the oxidizing microorganisms. Based on these results, the developed materials show great potential as multifunctional sulfur fertilizers, with ideal physical-chemical and processing properties for this kind of products and agronomic capacity to increase sulfate availability for plant uptake.